A Proposed Method for Simultaneous Measurement of Cuticular Transpiration From Different Leaf Surfaces in Camellia sinensis - Zhang, Yi; Chen, Xiaobing; Du, Zhenghua; Zhang, Wenjing; Devkota, Ananta Raj; Chen, Zijian; Chen, Changsong; Sun, Weijiang; Chen, Mingjie (Frontiers in Plant Science, 2020)
The plant cuticle is the major barrier that limits unrestricted water loss and hence plays a critical role in plant drought tolerance. Due to the presence of stomata on the leaf abaxial surface, it is technically challenging to measure abaxial cuticular transpiration. Most of the existing reports were only focused on leaf astomatous adaxial surface, and few data are available regarding abaxial cuticular transpiration. Developing a method that can measure cuticular transpiration from both leaf surfaces simultaneously will improve our understanding about leaf transpiration barrier organization. Here, we developed a new method that enabled the simultaneous measurement of cuticular transpiration rates from the adaxial and abaxial surfaces. The proposed method combined multi-step leaf pretreatments including water equilibration under dark and ABA treatment to close stomata, as well as gum arabic or vaseline application to remove or seal the epicuticular wax layer. Mathematical formulas were established and used to calculate the transpiration rates of individual leaf surfaces from observed exper¬¬¬imental data. This method facilitates the simultaneous quantification of cuticular transpiration from adaxial and abaxial leaf surfaces. By applying this method, we demonstrated that the adaxial intracuticular waxes and the abaxial epicuticular waxes constitute the major transpiration barriers in Camellia sinensis. Waxes analysis indicated that adaxial intracuticular waxes had higher coverage of very long chain fatty acids, 1-alkanol esters, and glycols which may attribute to its higher transpiration barrier than that of the abaxial intracuticular waxes.